Impact of the Lipopolysaccharide Chemotype of Salmonella Enterica Serovar Typhimurium on Virulence in Gnotobiotic Piglets - Splichalova, Alla (Toxins (Basel), 2019)
Salmonella Typhimurium is an enteric pathogen that causes acute and chronic infections in humans and animals. One-week-old germ-free piglets were orally colonized/infected with the Salmonella Typhimurium LT2 strain or its isogenic rough ΔrfaL, ΔrfaG or ΔrfaC mutants with exactly defined lipopolysaccharide (LPS) defects. After 24 h, the piglets were euthanized and the colonization of the small intestine, translocations into the mesenteric lymph nodes, liver, spleen, lungs, and bacteremia, along with changes in the ileum histology, and transcription levels of the tight junction proteins claudin-1, claudin-2, and occludin were all assessed. Additionally, transcription levels of IL-8, TNF-α, and IL-10 in the terminal ileum, and their local and systemic protein levels were evaluated. Wild-type Salmonella Typhimurium showed the highest translocation, histopathological changes, upregulation of claudins and downregulation of occludin, transcription of the cytokines, intestinal IL-8 and TNF-α levels, and systemic TNF-α and IL-10 levels. Depending on the extent of the incompleteness of the LPS, the levels of the respective elements decreased, or no changes were observed at all in the piglets colonized/infected with Δrfa mutants. Intestinal IL-10 and systemic IL-8 levels were not detected in any piglet groups. This study provided foundational data on the gnotobiotic piglet response to colonization/infection with the exactly defined rough Salmonella Typhimurium LT2 isogenic mutants.